Green leaf protein - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Green leaves could provide a large part of our protein requirements at a fraction of the cost of more traditional protein foods. A small UK relief agency 'Find Your Feet Ltd.', is already supporting the production of green leaf protein by village...